Marginalization And Subordination Of Women Workers At The Home-Based Batik Industry In East Java - Susanti, Emy (Opción, 2019)
Handmade batik production in Indonesia has been a part of community lives for centuries, mostly involving women. Nevertheless, the life of women craft- ers is very apprehensive and in poor condition. This paper is intended to ana- lyze the marginalization of women in the handmade batik home-based indus- try. This paper also aims to reveal the subordination of women workers in the community of the handmade batik home-based industry. Using a sociological and feminist perspective, this paper focuses more on social interaction and gender relations in the community of handmade batik home-based industries. The focus of the study is to reveal how women workers in the home-based batik industry have been put in subordinate and marginalized positions. This paper is based on research conducted in two Villages of East Java Province, namely in Bangkalan and Tuban Regency. The subjects of this study were all women involved in the batik home-based industry. Data collection techniques applied in this study were in depth interview technique on 20 informants and interview using questionnaire technique on 210 respondents chosen purpose- fully. The study reveals that the work of women crafters was marginalized toward the type of low-paid work. On the other hand, the types of work with a bigger wages were held by men, including marketing. This paper also argues that, although women hold a core position in the whole process of handmade batik production, they are in a subordinate position in the workplace and in the family. Women batik crafters do not get any work protection since the home industry is categorized as informal work and they are only considered as additional earners in the family.